Recycling of Plastic Waste, with Particular Emphasis on Thermal Methods—Review - Agnieszka Kijo-Kleczkowska; Adam Gnatowski (Energies, 2022)
The civilization development requires improvement of technologies and satisfaction of people’s needs on the one side, but on the other one it is directly connected with the increasing production of waste. In this paper, the authors dealt with the second of these aspects, reviewing the recycling of plastic waste, which can be processed without changing its chemical structure (mechanical recycling), and with changing its chemical structure (chemical recycling, of which thermal recycling). Mechanical recycling involves shredding the waste in order to obtain recyclate or regranulate that meets specific quality requirements. Chemical recycling consists of the degradation of the material into low-molecular compounds, and it can take place in the processes of hydrolysis, glycolysis, methanolysis by means of chemical solvents, and during thermal processes of hydrocracking, gasification, pyrolysis, combustion, enabling the recovery of gaseous and liquid hydrocarbons foundings in application as a fuel in the energy and cement-lime industry and enabling the recovery of thermal energy contained in plastics. The paper focuses on thermal methods of plastics recycling that become more important due to legal regulations limiting the landfilling of waste. The authors also took up the properties of plastics and their production in European conditions.